Academic Self-Efficacy and Academic Self-Esteem as Predictors of Academic Procrastination among Junior High School Students - Fransiska Dwi Nugraheni; Sutarto Wijono; Christiana Hari Soetjiningsih (Universitas PGRI Yogyakarta, 2026)
Academic procrastination poses a significant challenge to learning outcomes among adolescents, often stemming from psychological and motivational factors. This study investigates the extent to which academic self-efficacy and academic self-esteem simultaneously predict academic procrastination in students. A quantitative approach was employed, using multiple linear regression, to examine the predictive power of both variables. The participants consisted of 220 eighth-grade students from State Junior High School 4 Purworejo. Data were collected using three instruments: an academic procrastination scale, an academic self-efficacy scale, and an academic self-esteem scale. The results revealed that academic self-efficacy and academic self-esteem together significantly predicted academic procrastination (p < 0.001), accounting for 50.9% of its variance (R² = 0.509). These findings underscore the importance of fostering students’ academic self-efficacy and self-esteem to reduce procrastination and enhance academic performance. Keywords: academic self-efficacy, academic self-esteem, academic procrastination